Digital scientific marketing applied to the official Instagram of the Federal Uni-versity of Sergipe in reference to Covid-19 - Santos, Maria Egleide Silva; Fialho, Janaina; Paixão, Pablo Boaventura Sales (Ciência da Informação em Revista, 2023)
It presents an analysis of scientific digital marketing as a tool for the popularization of science through the official Instagram account of the Federal University of Sergipe. The publications that addressed subjects related to Covid-19, in the year 2020, were analyzed, totaling 155. The objective of this research is to identify digital scientific marketing actions in UFS Instagram publications aimed at the popularization of science. The research was carried out through a single case study, using descriptive bibliographic methodology with a qualitative-quantitative approach and content analysis, according to Laurence Bardin. The results pointed to four categories of posted content: suspension of activities, dissemination of actions to com-bat Covid-19, dissemination of university research and partnerships. Regarding the comments on the posts, four categories emerged: complaint, acknowledgment, demands and denialism. It is reported that UFS used scientific digital marketing to promote the popularization of science and sought to consolidate the image of credibility of its researchers.